Comparative Characteristics and Assessment of the Relations of Anthropometric Indicators and Motor Abilities of Girls` Basketball Players 12-14 Years Old - Chukhlantseva, N.; Cherednichenko, I.; Bruhno, E. (Central European Journal of Sport Sciences and Medicine, 2021)
Anthropometric indicators and motor abilities are significant components of the successful implementation of the physical potential of young basketball players. The aim of the study was to describe and compare anthropometric characteristics, indicators of physical and special preparedness for basketball players under the age of 12 and up to 14 years, to identify the presence and degree of relationship between these indicators in each group of athletes. Athletes (n = 50) were grouped in groups under 12 years (U12, 10.97 ±0.48 years; n = 24), and under 14 (U14; 12.96 ±0.49 years; n = 26), body height and body weight were measured, dexterity and indicators of special preparedness were tested and compared ("Throws into the basket from different positions", "Free Throws", "Ten eights"). U12 players showed lower performance than the U14 group in all tests except the "Free Throws" test. All athletes showed astrong correlation between jumping and dexterity (p < 0.01). The U14 athletes showed astrong (p < 0.01) and moderate (p < 0.05) relationship between the indicators of special preparedness. Assessment of indicators of physical development, physical and special preparedness of athletes, the study of the relationship of these indicators at different periods of ontogenesis will help rationally differentiate training loads, emphasize pedagogical influences and optimize the training process.